2021
DOI: 10.1016/j.celrep.2021.109559
|View full text |Cite
|
Sign up to set email alerts
|

RSPO2 inhibits BMP signaling to promote self-renewal in acute myeloid leukemia

Abstract: Highlights d RSPO2 is a regulator of AML cell self-renewal d RSPO2 acts as a BMP antagonist instead of as a WNT agonist in AML d High RSPO2 expression is a marker for adverse prognosis in AML

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 79 publications
2
25
0
Order By: Relevance
“…We recently showed that RSPO2 inhibits BMP signalling in AML cells to maintain self-renewal and prevent differentiation independent of WNT signalling (26). We therefore asked whether RW d could reduce endogenous RSPO2 activity of THP-1 AML cells to upregulate BMP signalling and thereby induce monocyte to macrophage (CD11B + ) differentiation.…”
Section: Rw Dendrimer Induces Thp-1 Differentiation and Inhibits Cell...mentioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that RSPO2 inhibits BMP signalling in AML cells to maintain self-renewal and prevent differentiation independent of WNT signalling (26). We therefore asked whether RW d could reduce endogenous RSPO2 activity of THP-1 AML cells to upregulate BMP signalling and thereby induce monocyte to macrophage (CD11B + ) differentiation.…”
Section: Rw Dendrimer Induces Thp-1 Differentiation and Inhibits Cell...mentioning
confidence: 99%
“…Given that RSPO2 antagonizes BMP4 signalling (14,26), we expected that RW d derepresses RSPO2-mediated inhibition of BMP4 signalling. To test this prediction, we employed human hepatocellular carcinoma (HEPG2) cells, which harbor very low endogenous RSPO2 expression (14).…”
Section: Rw Dendrimer Derepresses Bmp4-bmpr1a Signallingmentioning
confidence: 99%
See 3 more Smart Citations